Prognostic value of diagnostic criteria for familial hypercholesterolemia in men and women with dyslipidemia - Z. F. Kim; A. S. Galyavich; D. I. Sadykova; L. M. Nurieva (Российский кардиологический журнал, 2023)
Aim. To analyze the prognostic value of the Dutch Lipid Clinic Network (DLCN) and Simon Broome Register (SBR) screening criteria for familial hypercholesterolemia (FH) in men and women with dyslipidemia.Material and methods. The study included 1233 patients with dyslipidemia.Biomaterial samples from 421 patients were studied using Next Generation Sequencing (NGS) to identify FH-associated genes. Statistical analysis was carried out using the StatTech v program. 3.1.6 (OOO Stattekh, Russia).Results. The most significant factors for predicting the FH in men are the level of low-density lipoprotein cholesterol (LDL-C) (1,77 times), positive family history for coronary artery disease (CAD) (6,26 times), multivessel coronary artery disease (4,05 times); in women before menopause — LDL-C (1,77 times per 1 mmol/l) and/or family history of coronary artery disease (3,31 times), in menopausal women — total cholesterol level (1,79 times per 1 mmol/l), coronary artery disease (6,52 times) and/or family history of stroke (6,04 times), xanthomas (4,24 times). Acute myocardial infarction and/or coronary stenting, arcus senilis, extracranial artery atherosclerosis did not prove to be prognostically significant for FH diagnosis.Conclusion. Diagnostic criteria for potential FH vary among patient populations. Its diagnostic significance depends on sex, and in women, reproductive status.